Anti-inflammatory and antitumor activities of the chloroform extract and anti-inflammatory effect of the three diterpenes isolated from Salvia ballotiflora Benth - Nimsi Campos-Xolalpa; Ángel Josabad Alonso-Castro; Elizabeth Ortíz-Sanchez; Juan Ramon Zapata-Morales; Marco Martin González-Chávez; Salud Pérez (BMC, 2021)
Abstract Background Drugs used for the treatment of diseases associated with chronic inflammation, such as cancer and rheumatoid arthritis have the potential to cause undesirable side-effects, which might result in patients ending treatment prematurely. However, plants are a viable option for the treatment of inflammatory diseases. In this study, we assessed the in vivo and in vitro anti-inflammatory activity, and the antitumor effects of the chloroform extract of Salvia ballotiflora (ECL). The pro-apoptotic effects of ECL in CT26 cells were also determined. Methods The chloroform extract of Salvia ballotiflora (ECL) was standardized using 19-deoxyicetexone (DEOX) as a phytochemical marker. The anti-inflammatory activity of ECL was determined on acute and chronic inflammatory models using the TPA-induced mouse ear edema assay. The antitumor activity of ECL was evaluated by the subcutaneous inoculation of CT26 cells on the back of Balb/c mice. In vitro CT26 cell death induced by ECL was determined by Annexin V/propidium iodide staining assay using flow cytometry. ECL and the diterpenes isolated from the chloroform extract included 19-deoxyicetexone (DEOX), icetexone (ICT), and 7,20-dihydroanastomosine (DAM), which were tested in LPS-stimulated J774A.1 macrophages to quantify pro-inflammatory cytokine levels. The in vitro anti-arthritic activity of ECL was determined using the bovine serum protein (BSP) denaturation assay. Results ECL exerted anti-inflammatory activities in acute (84% of inhibition, 2 mg/ear) and chronic models (62.71%, at 100 mg/kg). ECL showed antitumor activity at 200 mg/kg and 300 mg/kg, reducing tumor volume by 30 and 40%, respectively. ECL (9.5 μg/mL) induced in vitro apoptosis in CT26 cells by 29.1% (48 h of treatment) and 93.9% (72 h of treatment). ECL (10 μg/ml) decreased levels of NO (53.7%), pro-inflammatory cytokines IL-6 (44.9%), IL-1β (71.9%), and TNF-α (40.1%), but increased the production of the anti-inflammatory cytokine IL-10 (44%). The diterpenes DEOX, ICT, and DAM decreased levels of NO (38.34, 47.63, 67.15%), IL-6 (57.84, 60.45, 44.26%), and TNF-α (38.90, 31.30, 32.83%), respectively. ECL showed in vitro antiarthritic activity (IC50 = 482.65 μg/mL). Conclusions ECL exhibited anti-inflammatory and anti-tumor activities. Furthermore, the diterpenes DEOX, DAM, and ICT showed anti-inflammatory activity by reducing levels of NO, TNF-α, and IL-6.